Upaya Meningkatkan Hasil Belajar Bermain Kasti Melalui Pola Gerak Dasar Lokomotor dan Manipulatif - Nurhikmah Nurhikmah (Universitas Lampung, 2019)
This research was a classroom action research conducted in 4 meetings in the first cycle, and the second cycle was designed through four stages, namely planning, action, observation, and reflection. The data of this study were the basic abilities of playing kasti as psychomotor data and the score of practice questions were as cognitive data. Observation was as effective data. The data source of this research was the IV grade pupils of SDN 1 Luwuk, Banggai Regency, 30 pupils. Data collection on the ability of playing kasti used the running, throwing and catching the ball, hitting the ball, and bouncing the ball techniques assessment sheets as well as multiple choice assessment sheets in the first cycle, and in the second cycle, the data collected were analyzed quantitatively. The quantitative results of the learning outcomes data of playing kasti in the initial conditions were 23.33% in the complete category with 7 pupils, and after being given the action, the results of learning to play kasti in the first cycle in the complete category was 70.73%, and the number of pupil who completed was 19 pupils, and in the second cycle there was an increase in the percentage of the results of playing kasti in the complete category of 93.33%, and the number of pupil who completed was 28 pupils, and 2 other pupils who did not complete were suffering physical disorders. Keywords: Learning outcomes, playing kasti, locomotor and manipulative basic movement patternsDOI: http://dx.doi.org/10.23960/jiip.v1i1.18018